PENERAPAN PENDEKATAN BERMAIN UNTUK MENINGKATKAN HASIL BELAJAR GERAK DASAR LARI - Risca Septiyani; Budhi Satyawan (PHEDHERAL, 2018)
The purpose of this study is to improve the basic motion of runing on  6 grade students SD N Laweyan No.54 Surakarta academic year 2017/2018.              This research is classroom action research (CAR). This research was conducted in two cycle and every cycle consist of plan, implementation, observation and reflection. The subject of this research is student in grade 6 of SD N Laweyan No.54 Surakarta that totaling 43 students, consist of 19 male students and 24 female students. Source of data derived from teachers, students and researcher. The validity of data use descriptive technique that based on qualitative analysis by percentage.              From the result of this research, the analysis obtained from initial condition of students who completed test only 18 students or 41,86% and not complete test is 25 students or 58,14 %, in the firt cycle students who completed to 32 students or 74,42% and not complete test is 11 students or 25,58 % , and in the second cycle students who completed to 36 students or 83,72% then 7 other students or 16,28%  have not completed with KKM is 75.              The conclution of this research is learning through play approach can improve learning result of basic motion run in 6 grade student of SD N Laweyan No.54 Surakarta academic year 2017/2018.